Analysis of microplastic content in sediments of two garden ponds located in the Mulawarman University Campus - Hamdhani, Hamdhani; Mangoting, Jelpratiwi; Ghitarina, Ghitarina (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
Plastic waste is the type of waste that is most commonly found in our environment. Plastic waste that decomposes and degrades into smaller particles is called microplastic. Small-sized microplastics (<5 mm) can accumulate in water sediments and are difficult to decompose, making this material remain in the environment for a long time. This research aims to determine the microplastic content in the sediment of the main gate garden pond and FEB garden pond at Mulawarman University. This research was carried out for 3 months starting from determining the research location until microplastic analysis. The research location was determined by purposive sampling in 2 garden ponds with 5 stations in each pond. Analysis of microplastic content in sediment was carried out using a separation method based on specific gravity using NaCl solution. Microplastic identification was carried out using a stereo microscope (8-16x magnification). The results of this research show that the types of microplastics found were fiber, fragments and films with the dominant type of microplastic being fiber. The highest abundance of microplastics was found in the FEB garden pond at 4,350 particles/kg, while in the main gate garden pond, it was 3,800 particles/kg.